1997
DOI: 10.1016/s0741-5214(97)70059-4
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy associated with residual dissection after surgical treatment of type A aortic dissection

Abstract: Our findings suggest that the coagulopathy worsened in proportion to the degree of dilatation of the dissected aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Another previous report 27 supports our finding that the D-dimer concentration is influenced by the presence of a thrombosed false lumen, but there was not an excessive deterioration of sensitivity for AADa in cases with a thrombosed false lumen. Shinohara et al reported that the sensitivity of the soluble elastin fragment for aortic dissection with and without a thrombosed false lumen was 0% and 88.9%, respectively.…”
Section: D-dimer Concentrationsupporting
confidence: 91%
“…Another previous report 27 supports our finding that the D-dimer concentration is influenced by the presence of a thrombosed false lumen, but there was not an excessive deterioration of sensitivity for AADa in cases with a thrombosed false lumen. Shinohara et al reported that the sensitivity of the soluble elastin fragment for aortic dissection with and without a thrombosed false lumen was 0% and 88.9%, respectively.…”
Section: D-dimer Concentrationsupporting
confidence: 91%
“…4 The application of stent-grafts to treat aortic dissection was first described by Dake et al 6 They used the graft to exclude blood flow from the true to the false lumen. Since then, several clinical studies have shown successful stent-graft repair of acute or chronic aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In the chronic phase of type B dissection, when the aneurysmal false lumen has evolved, surgical intervention is mandatory to prevent rupture. Additionally, when aortic dissection is accompanied by disseminated intravascular coagulation (DIC), surgical intervention is often necessary, [1][2][3][4] but it is associated with high mortality and morbidity owing to excessive blood loss during surgery. 5 Recent reports have suggested endovascular stent-grafting for type B aortic dissection as a potential alternative to surgical repair.…”
mentioning
confidence: 99%
“…Because the abnormal coagulation continued even after DIC treatment, the patient was diagnosed with a hematoma. Nakajima et al indicated that the residual dissection after surgical treatment of Stanford type A aortic dissection will decrease coagulation, which is a risk for DIC development [14]. Although the coagulation test results were not examined before hospitalization, the platelet counts were ≤ 100,000/μL for 2 years.…”
Section: Discussionmentioning
confidence: 99%